2005
DOI: 10.1007/s11123-005-2213-y
|View full text |Cite
|
Sign up to set email alerts
|

Product Market Competition, Skill Shortages and Productivity: Evidence from Canadian Manufacturing Firms

Abstract: In this paper, we estimate the impacts of product market competition and skill shortages on the productivity level performance of Canadian manufacturing firms. We use firms' perceptions of their competitive environment from the Statistics Canada 1999 Survey of Innovation to measure product market competition and skill shortages. We argue in the paper that such perceptions are important for productivity level performance. After controlling for other factors, we find that product market competition has a positiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
31
0
1

Year Published

2005
2005
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 51 publications
(33 citation statements)
references
References 17 publications
1
31
0
1
Order By: Relevance
“…Prior literature documents that firms improve productivity with the experience they accumulate as they age (see, for example, Haltiwanger et al 1999;Bulan et al 2010). Further, extant literature documents industry structure and competition (Tang and Wang 2005;Bulan et al 2010) and research and development expenditure (Griliches 1986;Bulan et al 2010) to have significant impact on productivity. We also include Leverage to control for risk (Ashbaugh-Skaife et al 2009) and PE Ratio as a proxy for future growth opportunities (Cragg and Malkiel 1982;Chung and Charenwong 1991).…”
Section: Empirical Analysismentioning
confidence: 99%
“…Prior literature documents that firms improve productivity with the experience they accumulate as they age (see, for example, Haltiwanger et al 1999;Bulan et al 2010). Further, extant literature documents industry structure and competition (Tang and Wang 2005;Bulan et al 2010) and research and development expenditure (Griliches 1986;Bulan et al 2010) to have significant impact on productivity. We also include Leverage to control for risk (Ashbaugh-Skaife et al 2009) and PE Ratio as a proxy for future growth opportunities (Cragg and Malkiel 1982;Chung and Charenwong 1991).…”
Section: Empirical Analysismentioning
confidence: 99%
“…Lucifora and Origo () estimate these costs in the short‐run and long‐run, as well as the direct and indirect costs of skill shortages in a set of European countries in the late 1990s, and conclude that costs generated by skill gaps average around 7% of GDP. A number of other studies have found that skill shortages negatively affect labor productivity, for example when firms fill jobs with over‐ or under‐skilled workers, or do not fill them at all (Tang and Wang ; Bennet and McGuinness 2009; Quintini ). The shortage of high‐skilled workers might decrease the innovation potential in the economy.…”
Section: Introductionmentioning
confidence: 99%
“…Disney et al (2003b), using the ARD, find that competition, measured as industry concentration and rents, raises the level and growth rate of TFP. Tang and Wang (2005) found that a firm's perception of the level of competition it 29 Martin (1993) develops a model that shows the opposite; greater competition results in a smaller payoff from increasing marginal efficiency and therefore the less it is in the interest of the owner to put in place an incentive structure that induces the manager to reduce marginal cost. Spence (1984) similarly shows that as the number of firms in the market increases (and the expected sales of each firm decreases) then the incentive to invest in cost reduction falls.…”
mentioning
confidence: 99%